1968
DOI: 10.1088/0022-3727/1/6/302
|View full text |Cite
|
Sign up to set email alerts
|

Electron penetration and the atomic number correction in electron probe microanalysis

Abstract: The number of ionizations on a given j shell in any electron-bombarded target has been calculated analytically by means of the Bethe formulae. A general formula for the atomic number correction has been derived in the form of an equation using parameters that are functions of target composition and accelerating voltage. This equation allows the calculation of the penetration effect to be readily carried out. The electron range, in terms of beam energy, has also been calculated. Finally, it is shown that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 10 publications
1
41
0
2
Order By: Relevance
“…The total intensity Ix of element X is given by the sum of (2) and (4) (11) and (12) it is clear that strictly speaking the extrapolated value of the uncorrected mass concentration ratio (11) is not equal to the exact ratio (12 It has been shown that for a perfect plane parallel foil the linear term of fluorescence emission equals zero (11 = 0) [5]. Hence If = fB = 0 so that from (11) and (12) it is clear that for T or Ix approaching zero (CA/CB)' == (CA/CB) without any assumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The total intensity Ix of element X is given by the sum of (2) and (4) (11) and (12) it is clear that strictly speaking the extrapolated value of the uncorrected mass concentration ratio (11) is not equal to the exact ratio (12 It has been shown that for a perfect plane parallel foil the linear term of fluorescence emission equals zero (11 = 0) [5]. Hence If = fB = 0 so that from (11) and (12) it is clear that for T or Ix approaching zero (CA/CB)' == (CA/CB) without any assumption.…”
mentioning
confidence: 99%
“…Hence If = fB = 0 so that from (11) and (12) it is clear that for T or Ix approaching zero (CA/CB)' == (CA/CB) without any assumption.…”
mentioning
confidence: 99%
“…Table 2 lists the compositions of the detected elements quantitatively estimated using the EDX spectra with a ZAF (atomic number, absorption, and fluorescence) correction method. 25) It was revealed that the ¡-Al 2 O 3 layers were occupying most of the area and that the sintering aids and the organic layers were slightly apparent on the particle surfaces, which suggests the organic layers existed only in the cracks and channels, not on all of the particle surfaces. This may indicate that the stearic acid reacted only with the AlN under-layers, and not with the ¡-Al 2 O 3 layers, as we had previously speculated.…”
Section: Fabrication Of Particles With Hybrid ¡-Al 2 O 3 / Organic Lamentioning
confidence: 97%
“…To take into account the surface roughness effect in our EPMA measurement, the composition data were corrected using the ZAF model. 21 This model considers atomic number (Z), absorption (A) and fluorescence (F) of the specimen to make correction of the EPMA data. In our study a two times iteration was used during the calculation that makes it ZAF2 correction model.…”
Section: þ2mentioning
confidence: 99%